Mechanisms of pentazocine-induced ventilatory depression and antinociception in anesthetized rats - Satoko Kimura; Yoshiaki Ohi; Akira Haji (Elsevier, 2016)
This study was performed to clarify mechanisms underlying pentazocine-induced ventilatory depression and antinociception. Spontaneous ventilation and hind leg withdrawal response against nociceptive thermal stimulation were simultaneously recorded in anesthetized rats. Pentazocine decreased minute volume resulting from depression of the ventilatory rate and tracheal airflow, and prolonged the latency of withdrawal response. Pre-treatment of β-funaltorexamine, but not nor-binaltorphimine, significantly attenuated pentazocine-induced ventilatory depression, while either antagonist weakened its analgesic potency. Comparing with effects of fentanyl and U50488, the present results suggest that ventilatory depression induced by pentazocine is mediated by mainly μ receptors and analgesia by both μ and κ receptors.